Lip b 1 is a novel allergenic protein isolated from the booklouse, Liposcelis bostrychophila. Issue 6 (24th January 2017) - Ishibashi, O.; Sakuragi, K.; Fukutomi, Y.; Kawakami, Y.; Kamata, Y.; Sakurai, M.; Nakayama, S.; Uchiyama, H.; Kobayashi, H.; Kojima, H.; Inui, T.
Abstract: Background: Booklice, belonging to the order Psocoptera, are small household insect pests that are distributed worldwide. Liposcelis bostrychophila, a common home‐inhabiting species of booklouse, infests old books, sheets of paper, and stored food. Recent entomological and serological studies demonstrated that L. bostrychophila accounted for the majority of detectable insects in house dust and could be a potent inducer of respiratory allergy. Our recent proteomic analysis identified a potent allergenic protein from L. bostrychophila, designated Lip b 1, and determined its partial amino acid sequences. Methods: Cloning of cDNAs for Lip b 1 was performed by large‐scale transcriptome analysis (RNA‐seq) and subsequent reverse transcription polymerase chain reaction. The full‐length amino acid sequences deduced from Lip b 1 cDNAs were bioinformatically analyzed. The recombinant proteins of glutathione S ‐transferase (GST)‐fused Lip b 1 were analyzed by Western blot and enzyme‐linked immunosorbent assay. Results: Lip b 1 cDNAs encoding two types of 254‐amino acid proteins were cloned. The clones shared 87% identity, and the deduced molecular weights and isoelectric points were consistent with those determined in our previous study. The two types of Lip b 1 proteins in the GST‐fused form were similarly reactive with sera from allergic patients sensitized with L. bostrychophila . Conclusions: Lip b 1 is a novel protein possibly causing booklouse allergy.